How does Housing First catalyze recovery?: Qualitative findings from a Canadian multi-site randomized controlled trial. Issue 2 (2nd April 2016) - Macnaughton, Eric; Townley, Greg; Nelson, Geoffrey; Caplan, Rachel; Macleod, Timothy; Polvere, Lauren; Isaak, Corinne; Kirst, Maritt; McAll, Christopher; Nolin, Danielle; Patterson, Michelle; Piat, Myra; et al.
ABSTRACT: Qualitative narrative interviews were conducted with 195 participants with histories of homelessness and mental illness at baseline and at an 18-month follow-up. Participants were randomly assigned at baseline to Housing First (HF; n = 119) or treatment as usual (TAU; n = 76) in five Canadian cities. Changes in consumers' narratives over time were examined for 13 life domains (e.g., housing stability, typical day, social relationships). HF participants showed superior housing stability that led to three important transitions in their recovery journeys: (1) the transition from street to home (e.g., greater control over one's environment, becoming unstuck), (2) the transition from home to community (e.g., pursuing relationships, participating in the community), and (3) the transition from the present to the future (e.g., developing autonomy and hope). In spite of the gains experienced by many HF participants and some TAU participants, there was a subgroup of HF participants and many more TAU participants who experienced considerable difficulty making positive transitions. This research affirms the importance of housing and support for people with mental illness who are homeless but extends previous research by elucidating how HF enables participants to navigate important transitions in their recovery journeys. Once housing stability is achieved, other services (e.g., supported employment, education, and socialization) are needed to accelerate the transitions that participants strive to make in their lives.